Electromyographic activity of the mandible muscles at the beginning and end of masticatory cycles in patients with complete dentures - Goiato, Marcelo Coelho [UNESP]; Garcia, Alicio Rosalino [UNESP]; Santos, Daniela Micheline dos [UNESP] (Karger, 2008)
The aim of this study was to assess the electrical activity of the masseter and anterior temporal muscles in subjects with severe bone resorption at two different times: ( a) the initial period, with the complete dentures they had worn for over 10 years, and (b) the final period, 5 months after having new dentures put into place. Twelve asymptomatic subjects were asked to respond to the questionnaire, according to the research diagnostic criteria for temporomandibular disorders, before denture rehabilitation and 5 months after the new dentures were put in place. The electrical activity of the muscles was recorded during mastication in the initial and final period, using artificial food (Optocal). The operator monitored the 35 chewing cycles that were repeated to grind the artificial food. After wearing the new dentures for 5 months, the right anterior temporal muscle showed a statistical difference before and after denture rehabilitation at the beginning and end of mastication. Muscular capacity and ability reduced the electrical activity in the masseter muscles after rehabilitation. Copyright (c) 2008 S. Karger AG, Basel.
Keywords: mastication; electromyographic activity; mastication; complete denture